Implementación de un módulo para el cálculo de elementos de una obra de toma y diseño de canales en el Laboratorio Virtual de Fluidos, Hidráulica y Eficiencia Energética (FHEEL-V) - Melgar Guachisaca, Patricio Iván (2014)
The present work has as objective to elaborate an application web inside the Virtual Laboratory of Fluids, Hydraulics and Energy Efficiency (FHEEL-V). This application called DHYCOB, developed by means of the computer tool Visual Microsoft Studio.net 2010 and allows the hydraulic design of the following components: open channels, water storage, hydraulic elements and drainage. DHYCOB allows designing two types of storage: Receptions conventional (with conventional grid). Receptions caucasians (with bottom grid). The design starts with the dimensioning of the elements of the selected reception, until the analysis of the stability of the dam. DHYCOB allows finding the stable parameters of alluvial channels using the methodology proposed by Altunin.